Global trends and health system impact on polycystic ovary syndrome: a comprehensive analysis of age-stratified females from 1990 to 2021 - Zeng, Weiwei; Gan, Dali; Ou, Juanfeng; Tomlinson, Brian (Frontiers in Reproductive Health, 2025)
Polycystic ovary syndrome (PCOS) is a major factor in female infertility. The global burden of PCOS has generally been neglected due to insufficient data. This study aims to comprehensively assess the burden of PCOS among females aged 10–54 years globally from 1990 to 2021, to project trends for the next two decades, and to evaluate the impact of health system levels on PCOS prevalence. The incidence, prevalence, and disability-adjusted life years (DALYs) from the Global Burden of Disease (GBD) 2021 were analyzed, including global, sociodemographic index (SDI), GBD regions, health system levels, and national data. PCOS global burden escalated by 28% from 1990 to 2021. In 2021, the estimated annual percentage changes (EAPC) value of age-standardized rate of prevalence (ASPR), incidence, and DALYs were 0.77 (95% CI: 0.75–0.79), 0.74 (95% CI: 0.70–0.77), and 0.72 (95% CI: 0.68–0.75), respectively. High SDI regions showed elevated prevalence but slower growth (EAPC = 0.09) vs. low SDI regions, which exhibited the highest acceleration (EAPC = 1.23). Especially, the incidence and prevalence in the advanced health system were highest, but the most dramatic upward trend was observed in the basic level. The top three countries for ASPR were Italy (8,113.16 per 100,000 females, 95% CI: 5,757.74–11,265.85), Japan (6,334.11 per 100,000 females, 95% CI: 4,579.73–8,798.66), and New Zealand (5,689.13 per 100,000 females, 95% CI: 4,094.50–7,762.63). The incidence in adolescents aged 10–19 years was highest, warranting particular concern. This study underscored that health systems and adolescents require attention and strengthening as critical measures to control PCOS globally and to increase the fertility of women.